2012
DOI: 10.1136/bcr-2012-007138
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of severe fluorosis in an adult

Abstract: Dental fluorosis is defined as hypomineralisation of enamel resulting from excessive ingestion of fluoride (more than 1 ppm) during tooth development. Mild-to-moderate forms of dental fluorosis are often unnoticed by the patients whereas severe fluorosis presents with dark brown-to-black discolouration of teeth along with enamel pitting and hypoplasia. Such discolouration results in an unpleasing appearance as well as psychological distress to the affected individual. Dental fluorosis can be managed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The advantage of this technique is in its celerity in reaching the desired esthetic in cases of mild or moderate DF. However, these procedures employ a high‐speed rotary instrument, which can lead to excessive removal of the dental structure …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of this technique is in its celerity in reaching the desired esthetic in cases of mild or moderate DF. However, these procedures employ a high‐speed rotary instrument, which can lead to excessive removal of the dental structure …”
Section: Discussionmentioning
confidence: 99%
“…However, these procedures employ a high-speed rotary instrument, which can lead to excessive removal of the dental structure. 107,109 Gugnani et al 58 suggested the use of a resin infiltrant to esthetically improve DF stains. The efficacy of resin infiltration in arresting noncavitated caries lesions has been proven.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients, especially young patients, have higher expectations for the appearance of their front teeth. Many scholars 7,8) believe that veneers, especially porcelain veneers, are the best choice for the esthetic restoration of dental fluorosis 9) . A total of 328 teeth of 64 patients with dental fluorosis were selected for this study, including 34 cases with direct resin veneers (196 teeth) and 30 cases with porcelain veneers (132 teeth).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the continents of Africa and Asia there are excessively high amounts of fluoride present in their water content while if we talk about the continents of North America and Europe then we can say that there are comparatively lesser incidence of fluorosis as excessive amount of fluoride is not present in the water bodies. 8,9 Particularly since the last few years especially last 10 years the prevalence of fluorosis has increased multifold as there are a variety of products used particularly for oral cavity which have a higher quantity of fluoride present in them. There are several toothpastes present and several mouthwashes present which have an excess of fluoride amount in them and when someone uses them without supervision then that can lead to creating a problem for that person.…”
Section: Epidemiology Of Dental Fluorosismentioning
confidence: 99%